2018
DOI: 10.1111/jace.15780
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectric‐ferroelectric phase transition in lead‐free AgNbO3 ceramics for energy storage applications

Abstract: The high‐energy storage density reported in lead‐free AgNbO3 ceramics makes it a fascinating material for energy storage applications. The phase transition process of AgNbO3 ceramics plays an important role in its properties and dominates the temperature and electric field dependent behavior. In this work, the phase transition behavior of AgNbO3 ceramics was investigated by polarization hysteresis and dielectric tunability measurements. It is revealed that the ferrielectric (FIE) phase at room temperature poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 42 publications
(76 reference statements)
2
66
0
2
Order By: Relevance
“…It should be noted that the energy storage efficiency η also increases from 0.42 (AN) to 0.63 (LAN2) and 0.87 (LAN5) due to the remarkably increased E F , E A and reduced E F ‐ E A with the incorporation of La 3+ . The results demonstrate the Ag 1−3 x La x NbO 3 ceramics exhibit more attractive comprehensive energy storage performance (with both high W rec and η ) than most of the reported AgNbO 3 ‐based and other lead‐free antiferroelectric ceramics (Figure B), making it promising a candidate for energy storage applications.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It should be noted that the energy storage efficiency η also increases from 0.42 (AN) to 0.63 (LAN2) and 0.87 (LAN5) due to the remarkably increased E F , E A and reduced E F ‐ E A with the incorporation of La 3+ . The results demonstrate the Ag 1−3 x La x NbO 3 ceramics exhibit more attractive comprehensive energy storage performance (with both high W rec and η ) than most of the reported AgNbO 3 ‐based and other lead‐free antiferroelectric ceramics (Figure B), making it promising a candidate for energy storage applications.…”
Section: Resultsmentioning
confidence: 83%
“…The energy storage properties of the as‐prepared LAN ceramics in this work and some other lead‐free antiferroelectric ceramics in literatures. A, W rec and η ; B, energy storage properties of AN and other lead‐free antiferroelectric ceramics, 0.828(Bi 0.5 Na 0.5 )TiO 3 –0.72BaTiO 3 –0.10NaNbO 3 (BNTBT–NN), 0.89(Bi 0.5 Na 0.5 )TiO 3 –0.06BaTiO 3 –0.05(K 0.5 Na 0.5 )NbO 3 (BNT–BT–KNN), AgNbO 3 (AN), Ag AgNbO 3 –0.2%MnO 2 (ANMn), Ag 0.97 Bi 0.01 NbO 3 (BAN), AgNbO 3 –0.1wt%WO 3 (AWN), Ag(Nb 0.85 Ta 0.15 )O 3 (ANT) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] Besides this, phase transition from FE to AFE in AN ceramics have also been particularly investigated by revealing the existence of ferrielectric (FIE) phase. [65] Subsequently, Wei et al have confirmed the existence of submicron polar regions and twin boundary with numerous stacking faults in pure AN of orthorhombic lattice. The two kinds of ferroelectric domain in AN with critical temperature of 70 and 170 °C, respectively, have also significantly been observed, which can be identified as the primary reason for double P-E loop, finally reaching the ESD of 2.1 J cm −3 at 0.175 MV cm −1 and showing better performance, as shown in Figure 10d,e.…”
Section: Silver Niobate Based Systemsmentioning
confidence: 97%
“…The frequency independent peaks at 353 °C correspond to the transition between antiferroelectric (AFE) phase Pbcm and paraelectric (PE) phase Cmcm . The relaxor‐like dielectric peaks and corresponding loss drop at around 75 °C are generally recognized as the phase change from polar Pmc2 1 to nonpolar Pbcm , indicating the coexistence of ferroelectric (FE) and AFE property at room temperature, which previously was also claimed as ferrielectric state of ANO . Besides, there is an indetectable dielectric anomaly around 180 °C (clearly collected in the cooling curves shown in Figure S1, Supporting Information), which is defined as freezing temperature ( T f ) in recent studies, suggesting the residual local polar regions in the temperature range from 75 to 180 °C.…”
Section: Resultsmentioning
confidence: 81%